2014
DOI: 10.1590/s0102-8650201400150003
|View full text |Cite
|
Sign up to set email alerts
|

Collared Pecary (tayassu tajacu) as a new model of renal ischemic injury induced by clamping the renal artery

Abstract: PURPOSE:The use of the collared peccary as an experimental model for ischemic nephropathy. METHODS:A total of 12 collared peccary (Tayassu tajacu) was used and ischemic nephropathy was induced in six of these animals that constituted the experimental group (G1) while the other six formed the control group (G2). Ischemic nephropathy was induced surgically by partial occlusion of the left renal artery. The disease course was assessed by hematological tests, serum chemistry, urinalysis, ultrasound (US) and dopple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The anesthetic protocol used in this study produced adequate sedation without hemodynamic compromise, which would alter the flow measurements taken (all animals were monitored for cardiovascular changes using an electrocardiogram and blood pressure measurements). This anesthetic protocol was used with great success in the peccary by Pessoa et al, (2014) to collect adipose tissue, by Argôlo Neto et al, (2016) to collect bone marrow, and by Bezerra et al, (2014) in establishing a preclinical model of renal injury from renal artery clamping. Batista et al, (2009) reported that chemical tranquilization in the peccary significantly reduces heart rate, rectal temperature, biochemical parameters, and stress indicators, making it easier to manipulate the animal.…”
Section: Discussionmentioning
confidence: 99%
“…The anesthetic protocol used in this study produced adequate sedation without hemodynamic compromise, which would alter the flow measurements taken (all animals were monitored for cardiovascular changes using an electrocardiogram and blood pressure measurements). This anesthetic protocol was used with great success in the peccary by Pessoa et al, (2014) to collect adipose tissue, by Argôlo Neto et al, (2016) to collect bone marrow, and by Bezerra et al, (2014) in establishing a preclinical model of renal injury from renal artery clamping. Batista et al, (2009) reported that chemical tranquilization in the peccary significantly reduces heart rate, rectal temperature, biochemical parameters, and stress indicators, making it easier to manipulate the animal.…”
Section: Discussionmentioning
confidence: 99%
“…Peccaries (Tayassu tajacu, Linnaeus, 1758) are wild mammals belonging to the Tayassuidae family and Tayassu genus. They are found experimental models for evaluating the evolution of diseases, peccaries are a good alternative model for scientific investigations (Bezerra et al, 2014).…”
Section: Introduction mentioning
confidence: 99%
“…The collared peccary is highly adaptable to different environments, extremely robust and resistant to various diseases. These characteristics greatly favor their use in scientific investigations, as observed by Bezerra et al (2014) and Pessoa et al (2014), which used these animals as models for renal ischemic lesions and the isolation of mesenchymal cells derived from adipose tissue. Thus, these animals are more accessible alternatives for scientific studies than is the domestic pig (Sus scrofa domesticus) (Monteiro et al 2009) or mini pigs (Vodička et al 2005).…”
Section: Introductionmentioning
confidence: 99%